Aroma therapy Lavender Against Mother’s Nausea Vomiting - Olii, Nancy; Yanti, Febri Dwi; Salman, Salman; Nurhidayah, Nurhidayah (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2022)
Morning sickness is experienced by around 70-80% of pregnant women and is a phenomenon that often occurs at 5-12 weeks of gestation. Morning sickness is caused by an increase in the hormones estrogen, progesterone, human chorionic gonadotropin expenditure and can be reduced by administering lavender aromatherapy. The research objective was to determine the effectiveness of giving lavender aromatherapy to reduce vomiting and nausea in first trimester pregnant women. The research method used was a quasy experiment with a pretest-posttest approach with a control group design. The sampling technique used was quota sampling, the sample size being 30 first trimester pregnant women in the Limboto Health Center area which were divided into a control group and an experimental group. This study shows that there is an effect of giving lavender aromatherapy to reduce nausea and vomiting in first trimester pregnant women at the Limboto Health Center. Lavender aromatherapy can reduce nausea and vomiting in first trimester pregnant women which can affect the nerves in the hypothalamus to reduce nausea and vomiting